ADOLESCÊNCIA E SEXUALIDADE: UMA ANÁLISE DO DISCURSO DA MÍDIA SEGMENTADA - Assolini, Rita de Cassia Schultheis Trevisan (2009)
This study proposes a reflection about the treatment given to sexuality on the Atrevida and Capricho magazines, aimed at teenagers. To compose the body, starting from 62 editions, published in 1996 and 2006. In the social context, there is a growing concern with the issues of sexual and reproductive health, early pregnancy, unsafe abortion among children under 18 years. So, the objective of this work is to check what is the contribution of those magazines adolescents with regard to information and clarification on the subject sexuality and whether, given the time, there was a change in the way of treating the subject. It is also our interest to check which way the discourse on sexuality is constructed in such spaces, and therefore the use of discourse analysis as theoretical and methodological axis. We conclude that, despite the fact that the subject has been found on bouth magazines, the approach to the topic is restrict and there is no frequency or continuation about the subject. We can notice an afford to clarify about sexuality and to disseminate security behavior. However, the approach to the subjects are made, in many opportunities, in a very superficial way and following standards of talking about sexuality that are not able to include the subject in all his complexity.(A)